ANALISIS NILAI-NILAI KEISLAMAN DALAM LIRIK LAGU RELIGI "TOMAT (TOBAT MAKSIAT)" KARYA WALI BAND - Sa'adah, Naila Waridatus; Wahyudin, Muhammad Hafidz; Mulyana, Anida Zahra; Salzabila, Nadia Bilqis; Humaedi, Abdullah Harjiman (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze and describe the representation of Islamic values (akidah, syariah, dan akhlak) contained in the lyrics of the religious song "Tomat (Tobat Maksiat)" by Wali Band. The method used is qualitative descriptive with a textual content analysis approach. Primary data in the form of song lyrics were obtained through library research and documentation. The results of the analysis show that the lyrics of this song contain comprehensive values. Key findings show the dominance of akidah values, including Remembering the Hereafter (Zuhud) and Repentance (Nadamah), as well as moral values such as Self-Awareness (Muhasabah) and Piety. The message of faith (faith in the Last Day) was found to have a significant percentage. It is concluded that the song "Tomat (Tobat Maksiat)" is a very effective contemporary medium of da'wah, especially for the younger generation, because it successfully combines a deep religious message with light pop music and popular language (an acronym for Tobat Maksiat), in line with the mau'izhah hasanah method.